Equalização concorrente de canal para sistemas monoportadora com acesso múltiplo por divisão de frequência - Noronha, Tiago Baptista (2012)
This Master Thesis presents a novel equalization technique for single-carrier frequency domain multiple access (SC-FDMA) systems based on Concurrent Algorithm (which is considered the state of art in terms of channel equalization). The SC-FDMA transmitter and receiver models have been described in SystemC for simulation, where the equalization method is reconfigurable in the receiver in order to compare multiple techniques. The channel degradation effects have been simulated using MATLAB®, considering the Rayleigh model with Doppler dispersion following the classical Jakes spectrum, where the power delay profiles indicated by 3GPP for the LTE performance tests have been adopted (EPA5, EVA5, EVA70, ETU70 and ETU300). The simulation results prove that the use of the novel technique, mainly when combined with other ones already applied in this kind of system, e.g. linear interpolation, improve substantially the channel deconvolution process. The concurrent equalizer which has been proposed was able to perform the deconvolution on all of tested channels.